Cellular Conductors: Glial Cells as Guideposts during Neural Circuit Development - Colón-Ramos, Daniel A (Public Library of Science, 2008)
Glial cells rise to the forefront as key regulators that direct how neurons connect to one another when nervous system is built. A new article highlights the molecular and cellular mechanisms by which glia guide the exquisite architecture of the mammalian cerebellum.